The influence of cyano compound on liquid crystal blue phase range - Chojnowska, Olga; Dąbrowski, Roman (Photonics Letters of Poland, 2012)
Liquid crystal blue phase (BP) is interesting for fast light modulators and tunable photonic crystals. In this study the influence of mixture composition on the thermal stability of BP was investigated, especially the influence of cyano compound addition. The relationship between polymer stabilization possibility and cyano dopant was examined, too. It was shown that the cyano compound is not necessary to create blue phase and has no effect on polymer stabilization of blue phase. Full Text: PDF References H. Kikuchi, M. Yokota, Y. Hisakado, H. Yang, T. Kajiyama, "Polymer-stabilized liquid crystal blue phases", Nature Materials 1, 64 (2002)CrossRef H. Yoshida, Y. Tanaka, K. Kawamoto, H. Kubo, T. Tsuda, A. Fuji, S. Kuwabata, H. Kikuchi, M. Ozaki, "Optical and Thermal Characteristics of Nd:LuVO4 Grown by Floating Zone Method", Appl. Phys. Express, 2, 12501 (2009)CrossRef K. Z. Zheng, D. Shen, P. Huang, "Wide blue phase range of chiral nematic liquid crystal doped with bent-shaped molecules", New J. Phys., 12, 113018 (2010).CrossRef H. Kikuchi, H. Higuchi, "Fast Electro-Optical Switching in Polymer-Stabilized Liquid Crystalline Blue Phases for Display Application", SID07 Digest, 38, 1737-1740 (2007)CrossRef J. P. Sethna, in Theory and Applications of Liquid Crystals (edited by J. L. Ericksen and D. Kinderlehrer) (Springer-Verlag,1987), p. 305CrossRef P.P. Crooker, in Chirality in Liquid Crystals (edited by H.S. Kitzerow and C. Bahr)186-222 (Springer, New York, 2001)CrossRef P. R. Gerber, "Electro-Optical Effects of a Small-Pitch Blue-Phase System", Mol. Cryst. Liq. Cryst., 116, 197 (1985)CrossRef K. M. Chen, S. Gauza, H. Xianyu, S. T. Wu, "Submillisecond Gray-Level Response Time of a Polymer-Stabilized Blue-Phase Liquid Crystal", J. Display Technol., 6, 49 (2010)CrossRef S. T. Wu, D. K. Yang, Reflective Liquid Crystal Displays, New York: Wiley (2001) S. K. Hong, G. L. Lim, H. Kikuchi, "Thickness Dependence of Blue Phase Transition Behavior of Chiral Nematic Liquid Crystal", Mol. Cryst. Liq. Cryst., 511, 248 (2009).CrossRef S. K. Hong, H. S. Choi, S. Shibayama, H. Higuchi, H. Kikuchi, "Blue Phase Temperature Range at n-Cyanobiphenyl Homologue Chiral Nematic Liquid-Crystal Mixtures", Mol. Cryst. Liq. Cryst., 528, 32 (2010)CrossRef P. Kula, Synthesis and properties of terphenyl and quaterphenyl based chiral diesters; Liquid Crystals, in press. W. Rejmer, K. Czupryński, W. Drzewiński, "An Influence of Nematic Medium on Helical Twisting Power of Chiral Compounds", Mol. Cryst. Liq. Cryst., 547, 33 (2011).CrossRef H. Kaczmarek, P. Gałka, "Active Thermitic Material Discovered in Dust from the 9/11 World Trade Center Catastrophe", The Open Process Chemistry Journal, 1, 8 (2008).CrossRef